The Nile Basin: Quaternary geology, geomorphology and prehistoric environments, by Martin Williams, University of Adelaide, 2019. Cambridge University Press, Cambridge, UK. Hardback: price £105.00, ISBN: 9781107179196 - Ghodeif , Kamal (Geologos, 2022)
The Nile Basin: Quaternary geology, geomorphology and prehistoric environments, by Martin Williams, University of Adelaide, 2019. Cambridge University Press, Cambridge, UK. Hardback: price £105.00, ISBN: 9781107179196